0535 Evaluation of Insomnia Symptoms in a Double-Blind, Randomized, Placebo-Controlled Phase 3 Trial of Sage-217 in Postpartum Depression. (27th May 2020) - Mittal, A; Deligiannidis, K; Huang, M; Suthoff, E; Acaster, S; Fridman, M; Li, S; Gunduz-Bruce, H; Lasser, R; Campbell, A D; Bonthapally, V; Hodgkins, P; et al.
Abstract: Introduction: Postpartum depression (PPD) is a specifier of major depressive disorder (MDD) with peripartum onset. SAGE-217, an investigational, oral neuroactive steroid GABAA receptor positive allosteric modulator, demonstrated improvements in depressive and anxiety symptoms versus placebo in a Phase 3 trial in PPD (NCT02978326; ROBIN) and a pivotal trial in MDD (NCT03000530). In PPD and MDD, insomnia symptoms are key diagnostic features, comorbid sleep disorders are frequent, and insomnia is a common residual symptom. Here we conducted post-hoc analyses to assess insomnia symptoms in the ROBIN trial. Methods: Women (n=151) ages 18-45, ≤6 months postpartum, with PPD (major depressive episode beginning in 3 rd trimester or ≤4 weeks postpartum) and a Hamilton Rating Scale for Depression (HAM-D) total score ≥26, were randomized 1:1 to receive outpatient SAGE-217 30mg or placebo for two weeks, with 4 weeks follow-up. Change from baseline (CFB) in HAM-D score at Day 15 was the primary endpoint. Secondary endpoints included CFB in HAM-D at other time points and the Montgomery-Åsberg Depression Rating Scale (MADRS). Post-hoc analyses assessed HAM-D insomnia subscale (HAM-D-Ins) and MADRS individual insomnia item (MADRS-Ins) scores. HAM-D and MADRS measures were evaluated using a mixed-effects model for repeated measures. Safety and tolerability were assessed by adverse event (AE) reporting. Results: SAGE-217 demonstrated statistically significant Day 15 CFB versus placebo in HAM-D (primary endpoint: -17.8 vs. -13.6, p=0.0028), MADRS (-22.1 vs. -17.6, p=0.0180), and associated insomnia sub-scales/items (difference SAGE-217 vs. placebo; HAM-D-Ins: -1.003, p=0.0038; MADRS-Ins: -0.773, p=0.0116). Significant CFB in insomnia sub-scales/items favoring SAGE-217 were observed by Day 3 (HAM-D-Ins: -0.841, p=0.0142; MADRS-Ins: -0.710, p=0.017) and at Day 45 (HAM-D-Ins: -0.730, p=0.0207; MADRS-Ins: -0.636, p=0.0221). Most common (≥5%) AEs were somnolence, headache, dizziness, upper respiratory tract infection, diarrhea, and sedation. Conclusion: SAGE-217 demonstrated improvements in depression symptoms, including insomnia symptoms, and was generally well tolerated. Support: This study was sponsored by Sage Therapeutics, Inc.